(untitled) (American Journal of Islam and Society, 2004)
The author of this brief study on the political aspects of Southeast Asian Islam is a former State and Defense Department official who originally specialized in Latin American affairs before turning his attention to Southeast Asia. Rabasa now works for the RAND Corporation, a think tank with close links to the American national security community. The publisher’s target audience is security policy makers. Therefore, the studies it commissions are part analysis and part policy recommendations, whereby the former is often reduced to the bare essentials. It must be said that, in this case, Rabasa has succeeded in presenting a reasonably balanced picture in the space of a mere 80 pages. Already in his introduction the author observes that, apart from a sharpening divide between militant Islam and the West, the antagonism between radicals and moderates within the Muslim world has increased as well, and that strengthening moderate and tolerant tendencies within Islam should be supported. Rabasa sees both external and internal influences contributing to the rise of Islamic radicalism. In response to the intrusion of western culture, a heightened sense of Muslim self-awareness has found expression in identity- driven politics. A further polarizing element in Southeast Asian Islam is the Arabization process carried out by Wahhabi-inspired movements and with financial support from the Middle East. Other auxiliary factors to the formation of transnational networks connecting Muslim radicals are the Iranian revolution, the Afghan war, disillusion over the lack of progress in solving the Palestinian issue, and the eruption of ethnic conflicts involving Muslims in such areas as Bosnia, Chechnya, and Kashmir. Shifting to internal factors, Rabasa identifies different sets of causes for each Muslim country and Muslim-dominated region in Southeast Asia. In the case of Indonesia, the vacuum left by an imploding state structure following Suharto’s fall led to a sharpened political competition in which some saw Islam as a suitable vehicle to power. Malaysia witnessed increased rivalry between the ruling UMNO coalition and the Pan- Malay Islamic Party (PAS) for the vote of rural Malays, while in the Muslim-dominated southern regions of Thailand and the Philippines ...